Reforma amerykańskiego systemu podatkowego i jej znaczenie dla reformy polskiej - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1987)
The article contains two lines of considerations. The first concerns the analysis of the American tax reform of September 1986. The analysis is confined to several basic issues, such as shaping the extent of taxes and their generality. At the same time the author points out gradual decrease of progression and the reduction of the number of tax-rates as the phenomena having multiple and positive socio- -economic effects. Stress has also been laid on the way of treating inflation through the indexation of tax assessment basis what, in turn, makes it possible to tax real income. A characteristic feature of the American tax reform is an attempt to reach generality of taxation. Therefore many tax reliefs and reductions were eliminated; at the same time increased were the possibilities to stimulate the economy through taxes. The second line of considerations is concerned with the possibilities of adopting some solutions of the American tax reform for the purposes of actually prepared reform of general income and value-added tax in Poland. Some elements of the reform are contained in the theses for the second stage of the economic reform. Much more about the conception of both taxes can be found in financial writings. Both taxes are a significant element of the economic reform in general. Hence, the author stresses the need to undertake a thorough assessment of foundations of American tax system and especially of its ties with economic, social and cultural policy. Many solutions of that system might well be adopted in the course of formulating the conception of the Polish tax reform. It is generally stressed that the American reform of taxation was a very important step and that it may be an impulse for rebuilding the economy.
The American tax reform and its significance for the Polish reform